Artistic Value in The Ritual Tradition of Dreadlocks Shaving in Dieng Kulon Village, Batur District, Banjarnegara Regency - Adrianus Fani (BELIEF: Sociology of Religion Journal, 2026)
The practice of dreadlocks shaving is regarded as a sacred custom that continues to be upheld by the inhabitants of Dieng Kulon Village, Batur District, Banjarnegara Regency, Central Java. This ceremony integrates aspects of artistry, faith, and the cultural identity of the local community. This study seeks to elucidate the artistic components of the dreadlocks shaving ritual tradition in Dieng Kulon village. The employed methodology is qualitative, utilising ethnographic techniques, including observation and interviews with Dieng traditional leaders who conduct the dreadlocks shaving, enabling researchers to analyse this custom within a wider artistic and cultural framework. Clifford Geertz's concept of cultural interpretation is used in this study. The artistic aspects of the dreadlocks shaving ritual tradition as presented at the Dieng Culture Festival (DCF) are what make this research unique. The emphasis is on the aesthetic aspect which together convert sacred rituals into dynamic performances. The results show that the artistic elements of the dreadlocks shaving tradition enhance the ritual's holiness while maintaining harmony between people, ancestors, and the natural world. The Dieng Kulon village community's ability to pass down cultural and spiritual values throughout generations in spite of changing social circumstances is demonstrated by the dreadlocks shaving custom.